Attitude estimation for artillery shells using magnetometers and frequency detection of accelerometers. (May 2022) - Fiot, Aurélien; Changey, Sébastien; Petit, Nicolas
Abstract: The article proposes a method to estimate the attitude of an artillery shell in free flight. It uses strapdown accelerometers and magnetometers, and circumvents the intrinsic inability of accelerometers to provide direction information during free flight by employing them not to measure the gravity but to estimate the velocity w.r.t. the air. This is achieved in an innovative way, through frequency detection applied to the pitch and yaw rotational dynamics generated by aerodynamic moments, directly visible on the accelerometers' signals. The determination of the shell's velocity without any ground-based position radar is a first contribution. The velocity variation gives information regarding the shell's orientation that complements the direction given by the 3-axis magnetometer. The two sources of information are combined into an attitude estimate by a specific nonlinear observer. Experimental results obtained with a gyrostabilized supersonic 155  mm shell are presented. Highlights: Velocity of symmetric projectiles can be measured in their attitude oscillations. Nutation and precession frequencies reveal the air velocity of the projectile. Frequency detection on accelerometer provides information for attitude determination. Instead of wind tunnels, onboard sensors could serve to calibrate aerodynamic models.